2018
DOI: 10.1590/1806-9282.64.12.1077
|View full text |Cite
|
Sign up to set email alerts
|

Upper vena cava syndrome secondary to giant atrial myxoma

Abstract: SUMMARY Cardiac myxoma is a benign neoplasm, which corresponds to the most common primary heart tumour, responsible for about 50% of the cases. In general, 75-80% of myxomas are located in the left atrium, 18% in the right atrium, and more rarely in the ventricles or multicentric. Right atrial myxoma, in particular, can obstruct the tricuspid valve, causing symptoms of right heart failure, peripheral oedema, hepatic congestion, and syncope. Systemic embolization occurs in 30% of cases, by either tumour fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Even though the recurrence of myxomas resected surgically is typically within the first 4 years, recurrence was also reported after 14 years (7). Pathologies caused by right atrial myxomas in the tricuspid valve after surgical excision have been reported to be completely reversible (11). However, in our case, significant tricuspid insufficiency continues even after six months.…”
Section: Discussionmentioning
confidence: 52%
“…Even though the recurrence of myxomas resected surgically is typically within the first 4 years, recurrence was also reported after 14 years (7). Pathologies caused by right atrial myxomas in the tricuspid valve after surgical excision have been reported to be completely reversible (11). However, in our case, significant tricuspid insufficiency continues even after six months.…”
Section: Discussionmentioning
confidence: 52%
“…5 Fifteen percent of atrial myxomas are found in the right atrium, usually attached to the interatrial septum. [8][9][10] While typical myxomas are easier to diagnose, some may have atypical features that make the diagnosis challenging. [11][12][13][14] A possible cause of secondary tumors in the right atrium can be the extension of an intraabdominal tumor, like a hepatocellular carcinoma or renal cell carcinoma with a direct invasion of the inferior vena cava and the right atrium.…”
Section: Diagnosis Of Cardiac Massesmentioning
confidence: 99%